Synergistic effect of electrical and chemical factors on endocytosis in micro-discharge plasma gene transfection. (31st May 2017) - Jinno, M; Ikeda, Y; Motomura, H; Isozaki, Y; Kido, Y; Satoh, S
Abstract: We have developed a new micro-discharge plasma (MDP)-based gene transfection method, which transfers genes into cells with high efficiency and low cytotoxicity; however, the mechanism underlying the method is still unknown. Studies revealed that the N-acetylcysteine-mediated inhibition of reactive oxygen species (ROS) activity completely abolished gene transfer. In this study, we used laser-produced plasma to demonstrate that gene transfer does not occur in the absence of electrical factors. Our results show that both electrical and chemical factors are necessary for gene transfer inside cells by microplasma irradiation. This indicates that plasma-mediated gene transfection utilizes the synergy between electrical and chemical factors. The electric field threshold required for transfection was approximately 1 kV m −1 in our MDP system. This indicates that MDP irradiation supplies sufficient concentrations of ROS, and the stimulation intensity of the electric field determines the transfection efficiency in our system. Gene transfer by plasma irradiation depends mainly on endocytosis, which accounts for at least 80% of the transfer, and clathrin-mediated endocytosis is a dominant endocytosis. In plasma-mediated gene transfection, alterations in electrical and chemical factors can independently regulate plasmid DNA adhesion and triggering of endocytosis, respectively. This implies that plasma characteristics can be adjusted according to target cell requirements, and the transfection process can be optimized with minimum damage to cells and maximum efficiency. This may explain how MDP simultaneously achieves high transfection efficiency with minimal cell damage.